2016
DOI: 10.1002/2015ja021941
|View full text |Cite
|
Sign up to set email alerts
|

Continuous solar wind forcing knowledge: Providing continuous conditions at Mars with the WSA‐ENLIL + Cone model

Abstract: Knowledge of solar wind conditions at Mars is often necessary to study the planet's magnetospheric and ionospheric dynamics. With no continuous upstream solar wind monitor at Mars, studies have used a variety of methods to measure or predict Martian solar wind conditions. In situ measurements, when available, are preferred, but can often be limited in continuity or scope, and so studies have also utilized solar wind proxies, spacecraft flybys, and Earth‐Mars alignment to provide solar wind context. Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 73 publications
4
13
2
Order By: Relevance
“…It indicates that the time profile of the estimated upstream solar wind is consistent with that of the typical ICME passage [e.g., Kataoka and Miyoshi , ]. Recently, comparison studies between the undisturbed solar wind observed by MAVEN and the WSA‐ENLIL+Cone model [e.g., Mays et al , ] are well performed by Dewey et al []. We thus also compare these solar wind proxies obtained from the MAVEN observations with the WSA‐ENLIL+Cone model (overplotted as red curves in Figures a–c).…”
Section: Dependence On Upstream Solar Wind Driverssupporting
confidence: 53%
“…It indicates that the time profile of the estimated upstream solar wind is consistent with that of the typical ICME passage [e.g., Kataoka and Miyoshi , ]. Recently, comparison studies between the undisturbed solar wind observed by MAVEN and the WSA‐ENLIL+Cone model [e.g., Mays et al , ] are well performed by Dewey et al []. We thus also compare these solar wind proxies obtained from the MAVEN observations with the WSA‐ENLIL+Cone model (overplotted as red curves in Figures a–c).…”
Section: Dependence On Upstream Solar Wind Driverssupporting
confidence: 53%
“…From the Earth vantage point, bright CME loops were observed in the southeast quadrant of the LASCO C2 field of view at 04:49 UT and 07:12 UT on 6 March 2015. The two CME merged en route to Mars, based on the LASCO C3 observations and the WSA-Enlil-cone simulations of the two CMEs Dewey et al, 2016]. At Mars, EUVM observed an M2.6 class flare that peaked around 05:50 UT on 6 March.…”
Section: Late February Through March Of 2015mentioning
confidence: 99%
“…Halekas et al, 2016] and/or use model data from WSA-Enlil-cone for estimates of the overall solar wind conditions. For the latter, there is ongoing research activity to improve the modeling accuracy of WSA-Enlil-cone for predicting the upstream conditions at Mars and validate the results with existing upstream solar wind observations [e.g., Falkenberg et al, 2011;Dewey et al, 2016].…”
Section: Periods Of Sep Activity Without Upstream Solar Wind Measuremmentioning
confidence: 99%
“…However, as MAVEN ascends or descends into the BS and other layering regions, there are time periods when there is no method to extract data on solar wind parameters such as the velocity of the plasma, particle density, pressure, temperature, and magnetic field properties. This is where solar wind forecasting models can be utilized to predict supplemental solar wind parameter values (e.g., Dewey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To test the model's validity during the two runs, MAVEN's solar wind ion analyzer and magnetometer were used to determine when MAVEN was in upstream solar wind. The SWIA instrument's absolute solar wind density measurements are subject to uncertainties due to ambiguities in the sensitivity calibration as mentioned in Dewey et al (). When comparing MAVEN's proton temperature values to WSA‐ENLIL+Cone estimated temperatures, values derived from SWIA for the orbited averaged data are at times overestimated because temperature is a partial moment of the solar wind plasma distribution.…”
Section: Introductionmentioning
confidence: 99%